Sosialisasi Pengelolaan Sampah Rumah Tangga Pada Ibu Rumah Tangga Di Kelurahan Sukarja Kecamatan Curup Timur - Yanuarti, Mira; Milanda B, Putri; Prisdinawati, Dwita (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
Ecological supportability can be accomplished assuming the local area is answerable for the neatness and magnificence of the general climate. The household should be the first place in society to handle waste management. Waste management is a very important job for housewives. The interview and outreach method was used to carry out community service activities with 21 PKH beneficiary housewives, 11 of whom were unaware of the significance of waste management. so that housewives benefit greatly from this activity in terms of their knowledge of waste management, waste sorting, waste processing for fertilizer use, and plastic waste submission to the Garbage Bank